2013
DOI: 10.1111/ctr.12096
|View full text |Cite
|
Sign up to set email alerts
|

The factors that influence attitudes toward organ donation for transplantation among UK university students of Indian and Pakistani descent

Abstract: Indian and Pakistani students are hesitant to donate organs because of multiple factors, which if addressed in a culturally relevant manner could substantially improve donation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 24 publications
3
57
1
Order By: Relevance
“…Previous studies have shown a number of different factors associated with attitudes towards organ donation. Altruism and ability to save lives, body wholeness and dignity, family attitudes, grief and fear from the donor family were some of the indicated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a number of different factors associated with attitudes towards organ donation. Altruism and ability to save lives, body wholeness and dignity, family attitudes, grief and fear from the donor family were some of the indicated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Gauher et al [23] also commented on the significance of religious and cultural barriers to organ donation among UK Muslims. Transplant advocates [22-29] have proposed corrective interventions: (1) reinterpreting religious scriptures, (2) reeducating faith leaders, and (3) utilizing media campaigns to overcome religious barriers to organ donation in Muslim communities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that many Muslims think living and deceased organ donation are not allowed in Islam, which can negatively influence their attitudes toward organ donation and transplantation . Other studies found that lack of public knowledge and understanding of the Islamic rulings on organ donation and transplantation is the major culprit . In general, Muslims are more willing to donate during their lifetime and to their family ; most concerns related to organ donation have to do with deceased donations.…”
Section: Resultsmentioning
confidence: 99%